Good morning, America - Power, Mark 1959- (GOST Books, 2019)
"Magnum photographer Mark Power has travelled expansively throughout the United States. A UK native, Power's perspective is that of an outsider. Observing the vast environmental and political landscape of the United States, Power has photographed the industrial heartlands of Appalachia, locations connected to climate change including one of the world's largest solar farms, an earth systems research facility, a major dam on the Colorado River and a Navajo Native American reservation among other diverse locations"--Amazon
Erscheint in 5 Bänden
Keywords: Power, Mark -- 1959-; Fotografie; USA; Photography, Artistic; United States / Social conditions / Pictorial works; Street photography / United States; United States / Pictorial works; Documentary photography / United States; Power, Mark / 1959-; Documentary photography; Social conditions; Street photography; United States; Photobooks; Pictorial works; Photobooks / England / 21st century; Bildband